Influence Of EWOM Information On Consumers’ Behavior in Instagram Social Network - Annisa Salsabila; Albari Albari (Journal of Business and Management Review, 2023)
Social network plays an important role in the dissemination of information related to products or services. The more information shared between consumers on social network, the more influential the consumer's attitude towards the product will be. This study aims to examine the influence of eWOM information on consumer behavior on the Instagram social network. eWOM information is indicated by attitudes towards eWOM information and the adoption of eWOM information, while consumer behavior is indicated from purchasing intentions and forwarding eWOM information (FeWOM). In this study, data was collected from Indonesians who are active Instagram users and have searched for information about products through reviews between consumers on Instagram. A total of 200 caomplete questionnaires were received. The sample sampling technique uses a non-probability sampling technique, namely conveniance sampling. The analysis uses the SEM (Structural Equation Modeling) model and is processed using the AMOS 22 program. The results showed that attitudes towards eWOM information had a significant effect on the adoption of information, purchase intention and forwarding eWOM information (FeWOM) and the adoption of eWOM information had a significant effect on purchase intentions. This study proposes that companies need to pay attention to and improve aspects related to eWOM information in the social media in order to provide long-term benefits for the company themselves.